The conclusion of international treaties in the Political Constitution of Panama: an analysis based on the law of foreign relations - Castro Montilla, José Roberto (2024)
The essay analyzes the provisions of the Political Constitution of Panama relating to the conclusion of international treaties, based on the law of foreign relations. To this end, it defines what the law of foreign relations is, according to specialized doctrine. It then identifies Panama's constitutional norms, under which it expresses its consent to be bound by an international treaty. Subsequently, it analyzes the way in which these provisions have been interpreted by the domestic authorities of the State, with special emphasis on the jurisprudence of the Supreme Court of Justice. Finally, the author sets out his considerations in relation to the points mentioned above.